Archbishop's Palace in Olmütz - Unknown:::Creator:::::::::::: (Hildburghausen; Germany; Kunstanst d. Bibliographisches Institut)
Engraving with a panoramic view of the Archbishop's Palace in Olmütz, Moravia, and the nearby landscape.